Strengthening National Character Values in Learning Citizenship Education Using The Snowball Throwing Method - Ardhiansyah, Wildhan; sumardjoko, bambang; Widyasari, Choiriyah (Graduate School of Universitas Negeri Malang, 2024)
Objective study This is For know strengthening mark character Spirit nationality in learning education citizenship with method snowball throwing . Method used in study This is method descriptive qualitative . Study carried out at school and studied inhabitant school in accordance with strengthening mark character Spirit nationality in learning education citizenship . Character value Spirit nationality integrated through syntax learning with method snowball throwing consisting of of 6 steps namely 1) convey purpose and motivate students , 2) present information , 3) organizing student to in groups learning , 4) guiding group work and study , 5) evaluation , and 6) provide assessment / reward . Research results This seen of the 3 meetings produced from analysis qualitative meeting First found 60% continued meeting second with percentage mark character 72% and ends at the meeting third with results mark character by 86%. Based on results the can concluded that adoption mark character Spirit nationality with method snowball throwing efficient and capable integrated in learning education citizenship.